Inter- and Intraobserver Reliability in the MRI Measurement of the Tibial Tubercle–Trochlear Groove Distance and Trochlea Dysplasia. (April 2015) - Skelley, Nathan; Friedman, Michael; McGinnis, Mark; Smith, Christopher; Hillen, Travis; Matava, Matthew
Background: The tibial tubercle–trochlear groove (TT-TG) distance and trochlear structure have become important radiographic measurements in the evaluation and management of patients with patellar instability. Many orthopaedic surgeons, however, do not have access to musculoskeletal radiologists and therefore must make such measurements independently. Purpose: To determine the intra- and interobserver reliability in the measurement of the TT-TG distance and the determination of the trochlear dysplasia index (TDI) between musculoskeletal radiologists and orthopaedic surgeons. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: Magnetic resonance imaging (MRI) was obtained from 63 patients with the clinical diagnosis of patellar instability (instability group) and from 53 patients without patellar instability (control group). Three radiologists and 2 orthopaedic surgeons blinded to the group assignment independently measured the TT-TG distance and determined the TDI. Each MRI was measured on 2 occasions separated by at least 1 week. Intraclass correlation coefficients (ICCs) were calculated to determine the intra- and interobserver reliability. Results: The instability and control groups were similarly stratified across age, sex, affected knee, athletic level, and body mass index. The mean TT-TG distances were 18.2 ± 5.6 mm and 13.7 ± 5.6 mm for the instability and control groups, respectively ( P < .001). The mean TDI for the instability and control groups was 2.1 ± 1.6 mm and 4.6 ± 1.3 mm, respectively ( P < .001). There was almost perfect intraobserver reliability for both the TT-TG distance and TDI measurements between the 2 time points for all observers (ICCs: ≥0.86 [TT-TG distance], ≥0.88 [TDI]). The interobserver reliability was also almost perfect between the orthopaedic surgeons and radiologists for both the TT-TG distance (ICC, 0.85 [95% CI, 0.82-0.88]) and TDI (ICC, 0.84 [95% CI, 0.79-0.88]). Conclusion: The results of this study suggest that the intra- and interobserver reliability in the MRI measurement of the TT-TG distance and TDI is high for both orthopaedic surgeons and musculoskeletal radiologists. In addition, the TT-TG distance may be lower than previously thought in patients with patellar instability.